2007
DOI: 10.1128/mcb.01225-07
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Shp2 in the Brain Leads to Defective Proliferation and Differentiation in Neural Stem Cells and Early Postnatal Lethality

Abstract: The intracellular signaling controlling neural stem/progenitor cell (NSC) self-renewal and neuronal/glial differentiation is not fully understood. We show here that Shp2, an introcellular tyrosine phosphatase with two SH2 domains, plays a critical role in NSC activities. Conditional deletion of Shp2 in neural progenitor cells mediated by Nestin-Cre resulted in early postnatal lethality, impaired corticogenesis, and reduced proliferation of progenitor cells in the ventricular zone. In vitro analyses suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
126
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 40 publications
(55 reference statements)
8
126
3
Order By: Relevance
“…SHP2 is an appealing molecule in the context of regulation of neurogenesis and gliogenesis, because it modulates not only the neurogenic (MEK-ERK), but also the gliogenic (gp130-JAK-STAT) signaling pathways by promoting MEK-ERK signaling while simultaneously inhibiting gp130-JAK-STAT signaling, respectively (6,7,26) (Fig. 1).…”
Section: Shp2 Enhances Neurogenesis and Inhibits Gliogenesismentioning
confidence: 99%
“…SHP2 is an appealing molecule in the context of regulation of neurogenesis and gliogenesis, because it modulates not only the neurogenic (MEK-ERK), but also the gliogenic (gp130-JAK-STAT) signaling pathways by promoting MEK-ERK signaling while simultaneously inhibiting gp130-JAK-STAT signaling, respectively (6,7,26) (Fig. 1).…”
Section: Shp2 Enhances Neurogenesis and Inhibits Gliogenesismentioning
confidence: 99%
“…These developmental syndromes are referred to as neuro-cardio-faciocutaneous syndromes as a result of overlapping phenotypes or "RASopathies" due to the abnormal regulation of the RAS/ MAPK pathway (Gelb and Tartaglia, 2006;Bentires-Alj et al, 2006;Tidyman and Rauen, 2009). In addition to growth, cardiovascular, and craniofacial defects, various studies have reported that nearly 50% of Noonan syndrome patients exhibit some form of neurocognitive impairment, suggesting an impact of the Shp2 GOF mutations in human brain development (Lee et Previous studies have shown a role for Shp2 in cell fate decisions by promoting neurogenesis and repressing astrogliogenesis in the developing hippocampus and cortex of the telencephalon (Gauthier et al, 2007;Ke et al, 2007). Moreover, Gauthier et al (2007) showed that germline Noonan syndrome mice (PTPN11 D61G/ϩ ) show more neurons and fewer astrocytes in the hippocampus and dorsal cortex at postnatal day 2, suggesting that Noonan syndrome mutations cause cellular brain abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, white matter regions and oligodendrocytes were not analyzed in these mice. In vitro studies have suggested different roles for Shp2 during OL proliferation and maturation (Kuo et al, 2010;Liu et al, 2011). Yet, the precise in vivo role for Shp2 or consequence of Noonan syndrome Shp2 GOF mutations during telencephalic oligodendrogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have recently shown that transient activation of the ERK1/2 signaling cascade mediates prosurvival effects of SHP-2 in mouse embryonic fibroblasts and in neural progenitor cells (14,15). To determine whether SHP-2 activity functions downstream of NMDARs and affects the ERK1/2 pathway in cortical neurons, we initially used the highly selective MEK inhibitor PD098059, as MEK is the kinase that activates ERK through dual phosphorylation of threonine and tyrosine residues (35).…”
Section: Activation Of Mek/erk1/2 Signaling Pathway Mediates Neuropromentioning
confidence: 99%
“…SHP-2 is known to localize in the cytosol and nucleus, and plays important biological functions in response to various growth factors, hormones, and cytokines (13). Recent studies have shown that activation of SHP-2 increases survival of various cell types, including neural progenitor cells and neurons, through activation of ERK1/2 (14,15). SHP-2 is thought to promote ERK signaling by dephosphorylating negative regulators of the Ras-ERK pathway, such as PAG/Cbp, Ras-GAP, or GAP-binding sites on receptor tyrosine kinases or Sprouty proteins (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%